Understanding the Clinical Features of Coronavirus Disease 2019 From the Perspective of Aging: A Systematic Review and Meta-Analysis - Yifan, Chen; Jun, Pu (Frontiers in Endocrinology, 2020)
Problems: An outbreak of novel coronavirus (2019-nCov) infection is now widespread in multiple countries. Compared with adult patients, elderly patients have not received enough attention. The aim of the meta-analysis was to assess the clinical characteristics of the elder patients with COVID-19. Methods: A deep literature search was performed in the databases until August 21, 2020. Risk ratio (OR) and 95% confidence intervals (CIs) were pooled using analysis models. Results: Three studies including 2046 infected patients were precisely evaluated and the results showed that the elderly group has a higher risk of hypertension, diabetes, and cardiovascular disease than the younger patients. And their total white blood cells are higher than that of the younger while their lymphocytes are relatively reduced compared with the younger. Conclusion: We comprehensively assessed the clinical characteristics of patients of different ages with COVID-19 and found that elder patients had a high risk of chronic cardiovascular and metabolism comorbidities. And the characteristic clinical manifestations and laboratory examinations of elderly patients support their excessive inflammation and weak immune defenses against 2019-nCoV. All these findings provided important information for understanding the general clinical characterization of the aging immune defense against virus and enhanced the public awareness of the prevention and treatment of elder patients in the COVID-19 pandemic.